Exploring the respiratory viral landscape beyond influenza and SARS-CoV-2: a 2020–2023 study in Fujian, China - You, Libin; Zhang, Zhengtao; Li, Hongjin; Weng, Yuwei (Frontiers in Public Health, 2025)
IntroductionIn this study, we investigated the local epidemiology and pathogen spectrum of acute respiratory infections caused by common respiratory viruses other than influenza virus (IFV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Fujian Province, China, from September 2020 to December 2023.MethodsSamples negative for IFV and SARS-CoV-2 were randomly selected from individuals presenting with influenza-like illness. These samples were tested for seven common respiratory viruses—human respiratory syncytial virus (HRSV), human parainfluenza virus (HPIV), human adenovirus (HAdV), rhinovirus (RV), human metapneumovirus, human coronavirus (HCoV), and human bocavirus. Quantification fluorescence polymerase chain reaction (qPCR) was used for detection.ResultsOne or more respiratory viruses were identified in 30.2% (n = 1,010/3,345) of the collected samples. RV was the most prevalent (10.9%), followed by HPIV (6.2%) and HRSV (4.5%). HPIV-3 was the dominant HPIV subtype (44.0%), and HCoV-OC43 was the predominant HCoV genotype (54.4%). Co-infections were observed in 2.9% (n = 96) of cases, with RV and HPIV co-infection being the most frequent. Age-specific variations were observed for most viruses, except for HCoV. HRSV exhibited a notably higher prevalence in young children (<5 years) and seniors (≥60 years), while HAdV was more common in children younger than 15 years. Regarding seasonal distribution, RV peaked in spring and autumn, whereas HRSV peaked in summer and autumn. No clear seasonal trends were observed for HPIV and HAdV. A negative correlation was observed between the incidence of IFV and the seven targeted respiratory viruses.DiscussionThese findings collectively underscore the importance of age-specific and seasonally tailored interventions, as well as the need for comprehensive diagnostic tools capable of simultaneously identifying multiple pathogens.